2000
DOI: 10.1034/j.1600-0579.2000.040103.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing of fine motor skills in dental students

Abstract: Manual skills form only a part of the capabilities required of future dentists, but they are a very important component, which should be tested. With regard to the dental specialties, the present study tested specialty-independent fine motor skills. No objective, practical solution has been found up to now. 88 dental students and, as a control group, 23 medical students were examined in the longitudinal study. In the course of the analysis, 4 fine motor tests were carried out at the beginning of the 2nd and 6t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 5 publications
9
47
0
4
Order By: Relevance
“…This fi nding is very important and in agreement with those of Gansky, 4 Luck 26 and de Andres 27 who feel that manual dexterity can be educated and improved by means of exercise and that tests to assess manual dexterity should be mainly used for identifying those subjects in need of a more careful, attentive and monitored …”
Section: Although This Study Was Not Intended To Describe a New Type supporting
confidence: 71%
“…This fi nding is very important and in agreement with those of Gansky, 4 Luck 26 and de Andres 27 who feel that manual dexterity can be educated and improved by means of exercise and that tests to assess manual dexterity should be mainly used for identifying those subjects in need of a more careful, attentive and monitored …”
Section: Although This Study Was Not Intended To Describe a New Type supporting
confidence: 71%
“…2,3,5,9,22 Rather than attempting to design another predictive test, the primary aim of this study was to establish whether dentists and dental students have problems with the interpretation of depth and distance. It is obvious that many did have significant problems.…”
Section: Discussionmentioning
confidence: 99%
“…1,7,8,10,11 Although it is acknowledged that manual dexterity is an essential and highly desirable quality for a dental student to possess, and studies have examined vision in dental populations, the number of studies that have examined interactions between manual dexterity and vision are few. 5,9,10 Good eyesight is essential to providing the best dental care for patients. 7,11 It is interesting that dentists and dental students as a group have been found to be recalcitrant regarding frequency of eye examinations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, studies have shown controversial results with regards to the professional success of the dental students. Predictive admission procedures reduce dropout rates, improve average academic performance and selectively exclude applicants who are unlikely to be successful later on.…”
Section: Introductionmentioning
confidence: 99%